Beobachtungen zum Phänomen der Hangversteilungen in Südwestaustralien - Dahlke, Jürgen (ERDKUNDE, 1970)
Steepening of slopes at the foot of inselbergs with cavities or overhangs has, up till now, been observed above all in south and central Australia. In western Australia, these forms also occur in the area of winter precipitation Me diterranean climate. Following a short review of a catalogue of possible explanations devised by Twidale, it is attempted, on the basis of observations of these forms, to throw more light above all on their group relationship to other micro forms and on the process and time in which they were formed. The following conclusions can be reached: 1. the exposition of overhangs from south to east, i. e. to the shaded side, which has been determined for south Australia, does not appear to apply with equal force in south west Australia; 2. peeled rock skins, which destroy the cavities, allow a conclusion to be drawn about the formation of the overhangs through subcutaneous weathering; 3. the presence of tafoni in the shaded area of the cavities implies the existence of a hard crust, but gives no indication of an ultimate influence of such a crust on the formation of the overhang. Despite some differences with reference to the conditions in south Australia, all the morphological results confirm Twidale's hypothesis of the two phase formation of the cavities by subcutaneous weathering and subsequent exposure.